Fractional Plasticity Model for Coarse Aggregates Incorporating Particle Breakage under Triaxial Loading - Jiangong Yang; Yifei Sun (Advances in Civil Engineering)
Fractional plasticity has been originally proposed for capturing the state-dependent nonassociated behaviour of sand, with no use of state variables and additional plastic potentials. However, for coarse aggregates, significant particle breakage would occur, which could influence the stress-strain behaviour of the material, by shifting the critical state line in the e−ln  p′ plane. In this note, an extension of the fractional plasticity for constitutive modelling of coarse aggregates is made by incorporating particle breakage under triaxial loading. The developed model is validated by simulating a series of laboratory test results of different coarse aggregates under triaxial loading, where a good agreement between the model simulations and test results is observed.